Evaluation of Operating Room Environment Contamination and Efficacy of 2% Chlorhexidine for Surgical Hand Scrubbing before and after Gowning and Gloving - Gobbo, Jessica Lais; Cardozo, Marita Vedovelli; Lacerda, Luciana de Cenço Corrêa de; Karcher, Débora Emy; Dias, Luís Gustavo Gosuen Gonçalves; Nardi, Andrigo Barboza de; Minto, Bruno Watanabe; Moraes, Paola Castro (Acta Scientiae Veterinariae, 2017)
Background: Human skin is colonized by various species of microorganisms, which makes them difficult to eliminate even with the use of antimicrobial drugs. Real efficacy of the antimicrobial product combined with incorrect administration of antibiotics, in addition to potential environmental contamination, are critical points for the establishment of postoperative infection or absence of it. The main objective of the present study was to evaluate the efficacy of surgical antisepsis using a 2% chlorhexidine brush during a surgery, detect operating room environmental contamination, and verify the existence of bacterial resistance to the antibiotics most commonly used in Veterinary Medicine. Materials, Methods & Results: In ten cases of the surgical routine, samples were collected concurrently at specific time points throughout 2 h of surgical procedure. To evaluate the efficacy of 2% chlorhexidine brush on hand scrubbing of a mock surgeon, swabs were used to sample the surface of the hands before and after gowning and gloving. Samples or their dilutions were inoculated onto blood agar and MacConkey agar plates. Contamination of the operating room was evaluated using BHI agar plates distributed through the room. After the incubation period, counts and biochemical tests were performed, and an antimicrobial disc susceptibility test was performed using antibiotics most commonly used in Veterinary Medicine. Discussion: Even though the surgical unit of the Veterinary Hospital “Governador Laudo Natel” is constantly sanitized, it is not free from microbial contamination. In the present study, there was no bacterial growth on MacConkey agar, which suggests absence of fecal contamination. Blood agar is a culture medium that provides optimal growth conditions to most pathogenic bacteria, which explains the higher microbial growth observed in this medium. Gram-positive cocci grew on blood agar forming grape bunch- and chain-like patterns, which indicates the possible presence of Staphylococcus sp. and Enterococcus sp. The results obtained to evaluate environmental contamination by means of BHI agar revealed growth of diverse microorganisms, with presence of Gram-positive cocci and Gram-negative rods. The biochemical tests indicated presence of microorganisms from various genera. About the evaluation of bacterial resistance to the antibiotics it was possible to observe high bacterial resistance to metronidazole, followed by ampicillin. Metronidazole has bactericidal activity against most of the anaerobic and facultative anaerobic bacteria, since the bacteria found were aerobic. As for ampicillin, it is considered a broad spectrum antibiotic, which indicates that the bacteria found can be resistant to this antibiotic. Clindamycin also resulted in bacterial high resistance, which shows that this drug was not effective against the Grampositive bacteria found in the samples studied. Enrofloxacin yielded high bacterial resistance indicating that wide use of this drug due to its intrinsic efficacy and safety might have contributed to the appearance of resistance. Results showed bacterial resistance to cephalexin, possibly indicating a lower efficacy in treatment against bacterial diseases, since a lot of the samples were Gram-positive. Bacterial resistance to ceftiofur was lower when compared to cephalexin; this can be related to the shorter time this drug has been in the market. The results revealed bacterial growth in the surgical environment, and verified the efficacy of 2% chlorhexidine for hand scrubbing. Spontaneous mutation and gene recombination contributes to the emergence of resistance is the indiscriminate use of antibiotics for the treatment of animals, which can contribute to bacterial resistance.